THE EFFECT OF ALTMAN Z – SCORE FINANCIAL RATIO ON STOCK PRICE (STUDY ON GO PUBLIC PLANTATION SUBSECTOR COMPANIES IN INDONESIA STOCK EXCHANGE) - Radityatama, Muhammad Fachri; Mustafa, Matrodji H. (Dinasti International Journal of Digital Business Management, 2019)
This study aims to examine and analyze the effect of the ratio - financial ratios Altman Z-Score on stock prices (study at the plantation subsector company that went public on the stock exchanges of Indonesia). The research data is annual data from 2014 until 2018. The sampling method used was purposive sampling. Of the population of 16 companies in the plantation subsector, 15 companies met the criteria plantation sub-sector into the sample. The analytical method used in this study is panel data regression. The results showed Working Capital to Total Assets (WCTA), Retained Earnings to Total Assets (RETA), Earnings Before Interest and Tax (EBITTA) and Market Value Equity to Book Value of Total Liabilites (MVEBTL) together - the same (simultaneous) effect significant positive stock price